2020
DOI: 10.1021/jacs.0c09922
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Union of Olefins, Organohalides, and Redox-Active Esters Enables Regioselective Alkene Dialkylation

Abstract: Multicomponent catalytic processes that can generate multiple C(sp 3 )C(sp 3 ) bonds in a single step under mild conditions, particularly if the catalysts and substrates are inexpensive, are highly sought-after in chemistry research for complex molecule synthesis. Here, we disclose an efficient Ni-catalysed reductive protocol that chemoselectively merges alkenyl amides with two different aliphatic electrophiles. Starting materials are readily accessible from stable and abundant feedstock and products are furn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 77 publications
(54 reference statements)
3
44
0
Order By: Relevance
“…Besides alkenyl bromides, alkenyl iodides worked with comparable reactivity ( 41 ); β-iodo acrylate and acrylamides were also competent coupling partners in this protocol ( 73 – 74 ). Notably, benzylic bromide can be employed to achieve regioselective 1,2-dialkylation of unbiased alkenes ( 75 ). , Finally, an array of fluoroalkyl iodides were applicable with moderate to high efficiency ( 76 – 83 ). Nevertheless, nonfluorinated tertiary alkyl halides were incompetent in this protocol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides alkenyl bromides, alkenyl iodides worked with comparable reactivity ( 41 ); β-iodo acrylate and acrylamides were also competent coupling partners in this protocol ( 73 – 74 ). Notably, benzylic bromide can be employed to achieve regioselective 1,2-dialkylation of unbiased alkenes ( 75 ). , Finally, an array of fluoroalkyl iodides were applicable with moderate to high efficiency ( 76 – 83 ). Nevertheless, nonfluorinated tertiary alkyl halides were incompetent in this protocol.…”
Section: Resultsmentioning
confidence: 99%
“…Catalytic three-component dicarbofunctionalization (DCF) reactions of olefins stand for a powerful approach to access functionalized molecules with the spontaneous installation of two different carbon fragments from readily available starting materials. However, efforts to explore their enormous synthetic potentials have often been hampered by the challenges associated with the regioselective control, particularly in the cases of electronically unbiased alkenes. Accordingly, a coordination strategy with pendant functional groups to stabilize transient metallacyles has been recently adopted, enabling excellent regioselective control in three-component DCFs of electronically unbiased alkenes. With regard to carboalkenylation reactions, ,,, Engle and Giri , groups independently utilized amino-quinoline and carbonyl as directing groups to develop Pd- and Ni-catalyzed three-component aryl-alkenylation of unbiased alkenes (Figure A). However, such a coordination strategy brings a new challenge to the stereoselective control of the newly formed allylic stereogenic centers. Recently, several groups reported three-component DCFs of electronically unbiased alkenes with two electrophiles via nickel-catalyzed cross-electrophile strategy, in which a number of directing groups were also utilized to control regioselectivity (Figure B). Specifically, our group reported a Ni-catalyzed asymmetric three-component reductive 1,2-alkylarylation of unbiased alkenes with (hetero)­aryl halides and alkyl iodide in the presence of Mn (Figure B) .…”
Section: Introductionmentioning
confidence: 99%
“…To date, the above-mentioned two strategies are still not able to access the trans -dialkylation of alkynes due to associated challenges, such as β-hydrogen elimination of alkylnickel intermediates, homocoupling of alkyl precursors, and hydroalkylation of alkynes ( Scheme 1c ). 17 Moreover, the regio- and stereoselectivity issues of intermolecular reactions impose an additional challenge for the dialkylation of alkynes. To this end, the use of two distinct alkyl electrophiles to sequentially couple across alkynes under reductive conditions renders an appealing alternative to access multialkylated olefins with defined stereochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…45 In 2020, we reported that 2-alkenylbenzaldimines were excellent substrates for regioselective dialkylation with benzyl bromides and alkylzinc reagents using Ni(cod) 2 (Scheme 8). 46 Concomitantly, Koh et al 47 disclosed a Ni-catalyzed dialkylation of alkenylquinolinamides with redox active esters. Our dialkylation reaction was highly efficient and could be conducted with 500 ppm catalyst, registering up to 2 × 10 3 catalytic turnover number (TON) and 165 h −1 turnover frequency (TOF) at room temperature.…”
Section: Introductionmentioning
confidence: 99%